Analysis of Risk Factors for Stunting in Toddlers in South Tapanuli Regency in 2024 - Evi Irianti; Melva Melva (Yayasan Adra Karima Hubbi, 2025)
Stunting is a major public health issue with long-term effects on the quality of human resources. The prevalence of stunting in South Tapanuli Regency increased from 30.8% in 2021 to 39.8% in 2022. This study aims to identify risk factors contributing to stunting in toddlers. The study employs a cross-sectional design with a correlational approach. The sample consists of 350 toddlers selected through purposive sampling, with data collected via structured interviews. The main contributing factors to stunting include a history of low birth weight (p=0.009), the introduction of complementary feeding before six months of age (p=0.000), and incomplete immunization status, which increases the risk of stunting with an odds ratio (OR) of 2.510. Virtual care is associated with a stable or improved HRQOL and patient and family satisfaction in pediatric T1DM. Decision makers need to consider expanding virtual access to pediatric diabetes care that can improve equitable access to quality care across healthcare systems globally.